2016
DOI: 10.1080/1828051x.2016.1241132
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the semi-feral Marismeño horse breed assessed with microsatellites

Abstract: Marismeño horses originated from primitive horses living around the marshes of the Guadalquivir River in Southern Spain. Throughout their evolution, they have experienced crosses with other breeds, first with horses from North Africa and thereafter with other horses. However, they have not lost their ability to adapt to the demanding marsh environment. Recently, a studbook of the breed was established, and the Breeders Association started a conservation programme. To study the relationship of the Marismeño wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…McManus, et al [91] described that GCI computes the genetic contributions of all the identified founders; for this reason, it has been assumed that the animals, which, get higher values of GCI, also gather wider fractions of the gene pool of the founding population. In our case, the higher GCI value was for PRá horse breed (11.50 ± 3.76), (9.74 ± 1.28 for Spanish horse breed) and (9.38 ± 5.88 for Há horse breed), which supports the higher contribution to the founding gene pool of PRá horses than PRE horses to the conformation and development of the Há horse breed, as it has been suggested by our results and other authors [66].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…McManus, et al [91] described that GCI computes the genetic contributions of all the identified founders; for this reason, it has been assumed that the animals, which, get higher values of GCI, also gather wider fractions of the gene pool of the founding population. In our case, the higher GCI value was for PRá horse breed (11.50 ± 3.76), (9.74 ± 1.28 for Spanish horse breed) and (9.38 ± 5.88 for Há horse breed), which supports the higher contribution to the founding gene pool of PRá horses than PRE horses to the conformation and development of the Há horse breed, as it has been suggested by our results and other authors [66].…”
Section: Discussionsupporting
confidence: 91%
“…The Mediterranean breeds considered in the study (PRá, PRE, and Há horse breeds) present strong differential physiological, behavioural and morphological differences [ 5 , 6 , 10 , 12 , 65 ] which are closely related to the geographical locations in which they locate and have developed along the course of History. This distinction and the closest link between PRá and Há horses was also supported at a genetic level by Pablo Gómez, et al [ 66 ]. This close connection between North African horses and those inhabiting in the Southern territories of the Iberian Peninsula has been reported to have occurred since prehistorical times and before the commercial routes established by the Greek and the Phoenician colonies took place.…”
Section: Discussionsupporting
confidence: 55%
“…Most studies of horses that have utilized STRUCTURE have examined a small number of breeds, often from a specific geographic locality (Barcaccia et al, 2013; Berber et al, 2014; Bömcke, Gengler, & Cothran, 2011; Conant et al, 2012; Cothran et al, 2011; Galov et al, 2013; Janova et al, 2013; Khanshour, Conant, et al, 2013; Khanshour et al, 2015; Koban et al, 2012; Kusza et al, 2013; Lopes et al, 2015; Mackowski, Mucha, Cholewinski, & Cieslak, 2015; Mujica, 2006; Pablo Gómez et al, 2017; Pires et al, 2016; Prystupa, Juras, Cothran, Buchanan, & Plante, 2012; Rendo, Iriondo, Manzano, & Estonba, 2012; Sereno, Sereno, Vega‐Pla, Kelly, & Bermejo, 2008; Tozaki et al, 2003; Uzans, Lucas, McLeod, & Frasier, 2015). The ∆ K obtained in these studies appeared reasonable for the number of breeds.…”
Section: Discussionmentioning
confidence: 99%
“…The more probable number of genetic clusters in our study was three, consistent with the Bayesian clustering of paternal lines [ 19 ]; although the outcomes of the structural analyses conducted using the Structure software depended on the marker used, the number of loci, the number of individuals per population (group), and the number of individuals in populations. The genetic structure may not be representative and cannot always correspond to the whole breed population [ 28 ]. Nevertheless, we prepared our data set representing the maternal lines with the greatest possible care.…”
Section: Discussionmentioning
confidence: 99%